ECONOMIC-SOCIAL INFRASTRUCTURE AND URBANIZATION DURING THE SOVIET ADMINISTRATION (EXAMPLE OF BUKHARA CITY) - Zakirovna, Hayotova Nafisa (PT. Antis International Publisher, 2024)
This article provides information about the development of economic and social infrastructure in the city of Bukhara during the Soviet government. Mainly during the war, the relocation of many factories and factories from the front zone to Bukhara created new opportunities for the expansion of the city's infrastructure and the development of industrial sectors. The article discusses the impact of these enterprises on the city structure, the construction of new housing and transport networks, and urbanistic changes. Also, the role and importance of Bukhara in the framework of the Soviet urban policy will be considered. The article aims to shed light on how it influenced the industrial development and urban development processes during the Soviet government.